(untitled) (Italian Journal of Public Health, 2010)
Background: Sexually transmitted infections represent a serious problem of public health. Chlamydia and Mycoplasms infections are involved in the pathogenesis of female infertility and in other serious gynaecologic and obstetric or neonatal complications. This study aims to analyze the prevalence of these infections in adult women and teenagers and to evaluate variations between 2010 and 2008. Methods: Women of reproductive age, sexually active, regardless of symptoms, examined only once for Chlamydia or, alternatively, for Mycoplasms vaginal/cervical infections, in 2008 (January-May) and in 2010 (January-May), at the Sandro Pertini Hospital were considered. Chlamydia was detected using Polimerase chain reaction; Mycoplasms were detected through culture. Patients were divided into women aged <20 years and ≥20 years. The Prevalence of Chlamydia and Mycoplasms infections was analyzed in both groups and compared (X2 test). Results: In 2008, 20 (1.46%) out of 1369 of this hospital’s patients aged ≥20 years versus 0 (0%) of 33 aged <20 years had Chlamydia infection. In 2010, the prevalence of Chlamydia infection was significantly higher in women <20 years old than in adult patients (10.3% versus 1.50%) (P = 0.0002). In 2008, 497 (36.9%) of the 1346 adult women and 7 (28%) of 25 patients <20 years old had Mycoplasms infection. In 2010, the prevalence of Mycoplasms infection was significantly higher in women under 20 years (56%) than in adult patients (34.8%) (P = 0.027). The prevalence of Mycoplasms infection amongst women aged <20 years was significantly higher in 2010 than in 2008 (P = 0.045). Conclusions: We observed an increased prevalence of Chlamydia and Mycoplasms infections in women aged <20 years in 2010 as compared with 2008, but only few of young women were undergoing clinical examinations. Sexual education and access to clinical services should be promoted in order to achieve control of sexually transmitted infections.